A comparison of analytical methods for measuring concentrations of 25-hydroxy vitamin D in biological samples. Issue 47 (22nd November 2018) - Rezayi, Majid; Ghayour-Mobarhan, Majid; Tavakoly Sany, Seyedeh Belin; Fani, Mona; Avan, Amir; Pasdar, Zahra; Ferns, Gordon A.; Abouzari-Lotf, Ebrahim; Amiri, Iraj S.
Abstract : Serum 25-hydroxyvitamin D (25(OH)D) is the principal circulating metabolite of vitamin D. Abstract : Serum 25-hydroxyvitamin D (25(OH)D) is the principal circulating metabolite of vitamin D. Several methods for measuring serum 25(OH)D have been reported. These methods include chromatographic methods (GC-MS, HPLC, and LC-MS), competitive protein-binding assay (CPBA), radioimmunoassay (RIA) and automated methods. In addition, biosensors have more recently been employed as potential candidates for routine analysis of 25(OH)D in serum. In this review, the common methods for quantification of 25(OH)D2 and 25(OH)D3 in biological samples, including the preparation of samples, are critically compared and discussed.